Two naturally occurring variants of the serotonin receptor gene HTR3C are associated with nausea in pregnancy - Goecke, Tamme W.; Ekici, Arif B.; Niesler, Beate; Loehberg, Christian R.; Hammer, Christian; Rappold, Gudrun; Schanze, Denny; Straub, Verica; Altmann, Hans-Harald; Strissel, Pamela; Strick, Reiner; Beckmann, Matthias W.; et al. (Acta obstetricia et gynecologica Scandinavica, 2010)
OBJECTIVE: To assess the association between pregnancy-associated symptoms and common single nucleotide polymorphisms (SNPs) in genes known to be involved in the pathogenesis of nausea and vomiting. - DESIGN: In a standardized, questionnaire-based interview, women selected from a control cohort for association studies were asked retrospectively about nausea and vomiting during their first pregnancy. - POPULATION: A total of 593 women who had completed at least one pregnancy and for whom germline DNA was available were selected. - METHODS: Eight SNPs in the serotonin receptor genes HTR3A, HTR3B, HTR3C, HTR3D, HTR3E, and NK1R (TACR1) were tested using polymerase chain reaction. The occurrence of nausea and vomiting was correlated with the patients' genotyping results and medical history parameters. - RESULTS: Both young age at first pregnancy and positive smoking status were significantly associated with vomiting and nausea during pregnancy. After adjustment for these two parameters, the two SNPs rs6806362 (odds ratio (OR) 1.38 per allele; 95% confidence interval (CI) 1.06-1.79; p = 0.017) and rs6807670 (OR 1.37; 95% CI 1.05-1.79 per allele; p = 0.023) were marginally associated with pregnancy-related nausea. None of the other polymorphisms showed any association. - CONCLUSION: Polymorphisms in the subunit gene HTR3C of the serotonin receptor may be involved in the pathogenesis of pregnancy-associated nausea.
Gesehen am 11.04.2023